Synthesis and Evaluation of Some Coumarin Based Schiff's Bases as Potential Antimicrobial Agents' - Vishakha Bansode; Meenakshi N. Deodhar (E-Journal of Chemistry)
A series of the title compounds 3-(4-(4, 5-dihydro-5-(substituted phenyl)-1H-3-pyrazolyl) phenylimino) methyl)-4-chloro-2H-chromen-2-one 5(a-g) have been synthesized. These compounds were characterized on the basis of their spectral (IR, 1H NMR) data and evaluated for antimicrobial activity in vitro against gram positive bacteria, gram negative bacteria and fungi. The compound (5b) was found to be the most active with MIC of 20 µg/ml against all the tested organisms.